Ancient plant DNA in lake sediments - Parducci, Laura; Bennett, Keith D.; Ficetola, Gentile Francesco; Alsos, Inger Greve; Suyama, Yoshihisa; Wood, Jamie R.; Pedersen, Mikkel Winther (The New phytologist, 2017)
Recent advances in sequencing technologies now permit the analyses of plant DNA from fossil samples (ancient plant DNA, plant aDNA), and thus enable the molecular reconstruction of palaeofloras.Hitherto, ancient frozen soils have proved excellent in preservingDNAmolecules, and have thus been the most commonly used source of plant aDNA. However, DNA from soil mainly represents taxa growing a fewmetres fromthe sampling point. Lakes have larger catchment areas and recent studies have suggested that plant aDNAfromlake sediments is a more powerful tool for palaeofloristic reconstruction. Furthermore, lakes can be found globally in nearly all environments, and are therefore not limited to perennially frozen areas. Here,we review the latest approaches and methods for the study of plant aDNA from lake sediments and discuss the progressmade up to the present.Weargue that aDNAanalyses add newand additional perspectives for the study of ancient plant populations and, in time, will provide higher taxonomic resolution and more precise estimation of abundance. Despite this, key questions and challenges remain for such plant aDNA studies. Finally, we provide guidelines on technical issues, including lake selection, and we suggest directions for future research on plant aDNA studies in lake sediments.